Sustainability management and strategy : an African casebook - Okoroba, Igazeuma Adikema; Mintah, Enoch Opare; Hinson, Robert (Productivity Press, 2025)
With Africa predicted to emerge as a leading market in the coming years, the debate on sustainability, especially on the mitigation of business impact on the continent's environment and society, cannot be underestimated. Prior to the worsening impact of climate change, the continent has historically been struggling to consolidate sustainability efforts in driving social and environmental protection caused by both foreign (majorly) and local business activities in the region. To capture current social and environmental injustice plaguing the African continent, SecretaryGeneral Prof. Petteri Taalas of the World Meteorological Organization (WMO) opined that "Africa is responsible for less than 10 percent of global greenhouse gas emissions, but it is the continent which is the least able to cope with the negative impacts of climate change. Heatwaves, heavy rains, floods, tropical cyclones, and prolonged droughts are having devastating impacts on communities and economies, with increasing numbers of people at risk."Sustainability Reporting Frameworks have empowered sustainability leaders, most especially Chief Sustainability Officers (CSOs), in organizations to develop practical strategies for leading sustainabilityrelated issues while driving systemic change for collective thinking towards mitigating the impact of climate change on society and the environment. While there is undoubtedly a plethora of standards, codes, and toolkits to help frame the sustainability drive, with leading CSOs around the globe sharing their lived experiences, the narrative for best practices, and what the content of sustainability initiatives and reporting should be have been skewed to the Western or advanced economies' narrative. This reporting has drowned out other continentspecific narratives that offer a diverse pool of perspectives and locally rich content on some sustainability actions and achievements, especially from CSOs. The role of business sustainability leaders and CSOs in Africa in positioning the continent as the "market of tomorrow" with sound and robust sustainability practices needs to be spotlighted. Owing to the gap, this book brings the urgency to light through case studies and stories from leading African businesses, while capturing their sustainability strategies and achievements. This book moves beyond the experience and context of business in advanced economies and responds to the need for an alternative narrative of sustainability leadership in Africa. The focus of this book is on the role of sustainability leadership over the last decade and discusses the contributions and challenges of navigating this multidisciplinary function in different sectors. The authors share their insight into this underresearched and underreported perspective highly relevant to business and sustainability, and environmental, social, and governance (ESG) reporting in a growing region like Africa.
Keywords: Management -- Africa -- Case studies.; Sustainable development -- Africa -- Case studies.; elektronické knihy; electronic books